Health system modelling research: towards a whole-health-system perspective for identifying good value for money investments in health system strengthening. Issue 2 (28th April 2019) - Verguet, Stéphane; Feldhaus, Isabelle; Jiang Kwete, Xiaoxiao; Aqil, Anwer; Atun, Rifat; Bishai, David; Cecchini, Michele; Guerra Junior, Augusto Afonso; Habtemariam, Mahlet Kifle; Jbaily, Abdulrahman; Karanfil, Ozge; Kruk, Margaret E; et al.
Abstract : Global health research has typically focused on single diseases, and most economic evaluation research to date has analysed technical health interventions to identify 'best buys'. New approaches in the conduct of economic evaluations are needed to help policymakers in choosing what may be good value (ie, greater health, distribution of health, or financial risk protection) for money (ie, per budget expenditure) investments for health system strengthening (HSS) that tend to be programmatic. We posit that these economic evaluations of HSS interventions will require developing new analytic models of health systems which recognise the dynamic connections between the different components of the health system, characterise the type and interlinks of the system's delivery platforms; and acknowledge the multiple constraints both within and outside the health sector which limit the system's capacity to efficiently attain its objectives. We describe priority health system modelling research areas to conduct economic evaluation of HSS interventions and ultimately identify good value for money investments in HSS.